Cover Image, Volume 115, Issue 18. Issue 18 (15th September 2015) - Eisenstein, Odile; Fliegl, Heike; Hopmann, Kathrin H.; Mennucci, Benedetta
<x xml:space="preserve">Abstract</x> The development of computational methods to investigate the non‐adiabatic dynamics of molecules under the influence of light is an active research field. Dynamics simulations play an important role in understanding a wide range of photophysical and photochemical processes; for example, the biologically important radiationless decay of nucleobases. On page 1215 (DOI:10.1002/qua.24891), Sebastian Mai, Philipp Marquetand, and Leticia González review SHARC, the newly released general trajectory surface hopping molecular dynamics method. SHARC is able to describe excited‐state dynamics in the presence of non‐adiabatic and spin‐orbit couplings, and, accordingly, this contribution puts special focus on the description of intersystem crossing dynamics.